STUDENTS’ PERCEPTION TOWARDS THEIR SKILL IN READING NOVELS IN WATTPAD APPLICATION - Herlina Herlina; Djunaidi Djunaidi; Yus Vernandes (Universitas PGRI Palembang, 2023)
The objective of this study was to investigate students' perceptions of their reading skills in novels on the Wattpad application. The research method employed a mixed-method approach, utilising questionnaires, interviews, and documentation to collect data. The population of the study consisted of 11th-grade students at PGRI Senior High School 2 in Palembang. The sample for this study was XI MIPA 1, comprising 36 students from PGRI Senior High School 2 in Palembang. The majority of students (64.7%) fell into the